110 Myocardial systolic strain and subclinical atherosclerosis in young adult life. (9th June 2011) - Lewandowski, A J; Lazdam, M; Davis, E; Poole, R; Diesch, J; Francis, J; Augustine, D; Banerjee, R; Suttie, J; Neubauer, S; Leeson, P
Abstract : Background: In the elderly, reduced left ventricular function is related to elevated carotid intima media thickness (IMT), a well-established subclinical marker of atherosclerosis. Cardiovascular magnetic resonance (CMR) allows for precise quantification of changes in myocardial structure and function. We therefore sought to determine if in young adults, without overt cardiovascular risk factors, there was already evidence of early changes in systolic function related to subclinical atherosclerosis. Methods: We studied 81 individuals (44 females, 37 males) without cardiovascular risk factors and with a mean age of 28.42±5.36 years (mean±SD). Peak mid-ventricular myocardial circumferential systolic strain and left ventricular mass adjusted for body surface area (LVM) were assessed by CMR. Carotid IMT was measured as a marker of subclinical atherosclerosis using ultrasound. Demographic and anthropometric characteristics were measured as well as metabolic parameters and peripheral and central blood pressure. Results: Individuals with reduced peak myocardial circumferential systolic strain had higher carotid IMT (r=0.392, p<0.001). Total cholesterol level and waist to hip ratio were both significantly associated with reduced myocardial strain. Increased LVM, central and peripheral systolic blood pressure, peripheral pulse pressure, glucose, triglycerides, age, body mass index and waist to hip ratio, as well as reduced high-density lipoprotein, were all significantly associated with increased carotid IMT (p<0.01). Males also had higher carotid IMT than females (mean±SD = 0.54±0.068 mm vs 0.47±0.042 mm, p<0.001). The association between carotid IMT and peak myocardial circumferential systolic strain was independent of gender, smoking, LVM as well as peripheral and central blood pressure measures. Conclusions: We have shown for the first time that subclinical changes in cardiac function and subclinical atherosclerosis are closely interrelated in young adults, with associations that extend to those in the normal range of cardiovascular risk. This study further establishes the ability of CMR to detect early changes in cardiovascular disease development.